Studi Pendahuluan Pytososiologi dan Keanekaragaman Vegetasi Pohon Desa Lanne, Kabupaten Pangkep - Muhammad Wiharto; Hamka L.; Syamsiah Syamsiah (Seminar Nasional LP2M UNM, 2019)
Abstract. The study of pythosociology and diversity of tree vegetation atau Lanne Village, Pangkep District had been done. In this study 98 species were found. Species A is the species with the highest (important value index) IVI with the highest frequency of attendance. J3 species has the highest second order IVI with the highest dominance value. There are 21 species that only have one individual who is also a species with a frequency of presence in only 1 plot. Species with 2 individuals were found as many as 14 species. Species found with individuals 1 and 2 are rare species. A total of 67 species were found that had an individual number of less than 10. The frequency of the presence of these species in observation plots ranged from 1 to 8 plots from 130 observation plots. The stand group formed based on the Brilloin index value is 3, namely group 1, group 2, and group 3. The stand group 2 has the highest number of transect members and also has the highest Brilloin diversity index value. The stand group with the least transect members is in the stand group 3. This stand group also has the lowest Brilloin index value Keywords: Pythosociology, diversity, tree vegetation, inportant value index